Dietary copper restriction in Wilson's disease. Issue 3 (March 2018) - Russell, Kylie; Gillanders, Lyn; Orr, David; Plank, Lindsay
Abstract Dietary copper restriction has long been considered an important aspect of treatment for Wilson's disease (WD). However, evidence supporting this approach is limited. There are no published randomised controlled trials examining this recommendation due to rarity of the disease and variable presentation. This review summarises current knowledge on the absorption and regulation of copper in humans and its relevance to patients with WD. Studies have demonstrated that as the level of dietary copper increases, the proportion absorbed decreases. This observation implies that 'high copper' foods that WD patients are generally advised to avoid would need to be consumed in large amounts to impact markedly on the quantity absorbed. Dietary copper restriction is unlikely to reduce the amount absorbed significantly and is not only difficult to manage but restricts food groups unnecessarily, detracting from the provision of substrates essential for improving nutritional status in a nutritionally compromised group. Medical management for WD is effective in compliant patients, allowing stabilisation of the liver disease. Based on current evidence, dietary copper restrictions in stable WD patients who are adherent to medical therapy are unnecessary with two food exceptions (shellfish and liver).